Comparison of Native Aspirates and Cytological Smears Obtained by EUS-Guided Biopsies for Effective DNA/RNA Marker Testing in Pancreatic Cancer - Benesova, Lucie; Halkova, Tereza; Bunganic, Bohus; Belsanova, Barbora; Zavoral, Miroslav; Traboulsi, Eva; Minarik, Marek (Pathology oncology research, 2020)
We compare two types of pancreatic carcinoma samples obtained by EUS-guided fine needle biopsy (EUS-FNB) in terms of the success rates and clinical validity of analysis of two most commonly investigated DNA/RNA pancreatic cancer markers, KRAS mutations and miR-21 expression. 118 patients with pancreatic ductal adenocarcinoma underwent EUS-FNB. The collected sample was divided, one part was stored in a stabilizing solution as native aspirate (EUS-FNA) and second part was processed into the cytological smear (EUS-FNC). DNA/RNA extraction was followed by analysis of KRAS mutations and miR-21 expression. For both sample types, the yields of DNA/RNA extraction and success rates of KRAS mutation and miRNA expression were evaluated. Finally, the resulting KRAS mutation frequency and miR-21 prognostic role were compared to literature data from tissue resections. The overall amount of isolated DNA/RNA from EUS-FNC was lower compared to the EUS-FNA, average yield 10 ng vs 147 ng for DNA and average yield 164 vs. 642 ng for RNA, but the success rates for KRAS and miR-21 analysis was 100% for both sample types. The KRAS-mutant detection frequency in EUS-FNC was 12% higher than in EUS-FNA (90 vs 78%). The prognostic role of miR-21 was confirmed in EUS-FNC (p = 0.02), but did not reach statistical significance in EUS-FNA (p = 0.06). Although both types of EUS-FNB samples are suitable for DNA/RNA extraction and subsequent DNA mutation and miRNA expression analysis, reliable results with clinical validity were only obtained for EUS-FNC.
Keywords: mutace; Proto-Oncogene Proteins p21(ras); Tissue Fixation; Female; Specimen Handling; Pancreatic cancer; ženské pohlaví; duktální karcinom slinivky břišní; Pancreatic Neoplasms; KRAS; DNA; lidé; nádory slinivky břišní; Mutation; EUS-FNA; Cytodiagnosis; Endoscopic Ultrasound-Guided Fine Needle Aspiration; biopsie tenkou jehlou pod endosonografickou kontrolou; miR-21; Male; nádorové biomarkery; Aged; mikro RNA; Carcinoma, Pancreatic Ductal; Biomarkers, Tumor; lidé středního věku; MicroRNAs; cytodiagnostika; senioři; mužské pohlaví; odběr biologického vzorku; protoonkogenní proteiny p21(ras); Middle Aged; fixace tkání; Humans